Anti-diabetic activity of embelin: Involvement of cellular inflammatory mediators, oxidative stress and other biomarkers - Naik, Suresh R.; Niture, Netaji T.; Ansari, Ansar A.; Shah, Priyank D. (Phytomedicine (Stuttgart), 2013)
Embelin (benzoquinone), an active constituent of methanolic extracts of the fruit of Embelia basal (Myrsinaceae), was studied in high fat diet (HFD)+streptozotocin (STZ) diabetic rats. Treatment of embelin (25 and 50mg/kg/day, p.o.) for 3 weeks to HFD+STZ diabetic rats elicited insignificant increase in body weight, reduced the elevated plasma glucose, glycosylated haemoglobin and pro-inflammatory mediators (interleukin 6 and tumour necrosis factor α) significantly. Furthermore, embelin treatment at both the doses significantly decreased the elevated malondialdehyde, restored depleted glutathione, antioxidant enzymes, superoxide dismutase and catalase in liver. The increased lipid profiles in HFD+STZ diabetic rats were also reduced by embelin treatment significantly. Embelin treatment to HFD+STZ diabetic rats also improved the altered histoarchitecture of β-islets of pancreas and hepatocytes. The embelin effect on progression of type 2 diabetes mellitus in rats appears to be through the inhibition of intracellular pro-inflammatory mediators, lowering of lipid profile and amelioration of oxidative stress. Considering the pharmacological activity profile of embelin, it is suggested that embelin be a useful diabetic modulator or adjuvant along with clinically effective anti-diabetic drugs in the treatment of type 2 diabetes mellitus and needs to be clinically evaluated on human subjects.